Utilising contextual memory retrieval cues and the ubiquity of the cell phone to review lifelogged physiological activities - Doherty, A; Tolle, K; Smeaton, A (2009)
In today's healthcare world where we react to conditions that have already developed, lifelogging technologies may offer a glimpse into a future world of proactive healthcare where symptoms of conditions are detected at much earlier stages. At the end of last year it was estimated that there were 4 billion cell phones in the world, in comparison to just over 1 billon PCs. In this paper we discuss a framework, which leverages the ubiquity of the cell phone, to aggregate data from multiple wearable biological sensors. This physiological lifelogged data can then be queried via an interface which utilises contextual memory retrieval cues to assist people remember what type of activity they were doing at a particular time. This may be helpful in the diagnosis of potential medical conditions or encourage wellness behaviours. Copyright 2009 ACM.